Pharmacokinetics and biosafety evaluation of a veterinary drug florfenicol in rainbow trout, Oncorhynchus mykiss (Walbaum 1792) as a model cultivable fish species in temperate water - Mallik, Sumanta Kumar; Shahi, Neetu; Pathak, Richa; Kala, Krishna; Patil, Prasanna Kumar; Singh, Bhupendra; Ravindran, Rajisha; Krishna, Nanitha; Pandey, Pramod Kumar (Frontiers in Pharmacology, 2023)
In two experimental trials; florfenicol pharmacokinetics following a single dose oral administration at 15 mg kg-1 fish body weight and biosafety through extended medicated feeding for a 30-d safety margin and a 20-d residual period analysis at 3, 5, and 10 times greater than the therapeutic dose 10 mg kg-1 biomass day-1 were studied in the rainbow trout, Oncorhynchus mykiss. Cmax µg kg-1 calculated for florfenicol were found to be 5360 in the intestine, 2890 in the gill, 2250 in the kidney, 973 in the liver, and 273 in plasma, obtained at Tmax of 16 h. The intestine had utmost AUC(tissue/plasma) of 13.83 and a prolonged half-life (t1/2ß) of 28.62 h. The highest AMR value in the kidney (0.327) showed a high level of biotransformation of florfenicol to its metabolite florfenicol amine. The ADR of florfenicol amine in muscle, in comparison to the parent drug florfenicol, indicated elimination of the medication mostly in the form of florfenicol amine with t1/2 of 16.75 h. The biosafety of florfenicol orally administered to rainbow trout recorded effective feed consumption, physiological responses, drug tolerance, and significantly low drug concentrations in the muscle of rainbow trout, thus its usage at 10 mg kg-1 fish body weight is recommended. In the study, the rapid absorption, greater bioavailability, enhanced dispersion, slower elimination, and biosafety of the drug form a significant basis for the florfenicol and its metabolite florfenicol amine as a useful antibacterial agent in aquaculture.